Use of Eucalyptus benthamii wood in the production of Oriented Strand Boards (OSB) Utilização da madeira de Eucalyptus benthamii na produção de painéis de partículas orientadas (OSB) - Gorski L.* (2015)
Use of Eucalyptus benthamii wood in the production of Oriented Strand Boards (OSB). This research aimed to produce OSB with particles of E. benthamii and mix of Pinus taeda and Pinus elliottii. The experimental plan involved five treatments composed of panels with three layers of particles and nominal density of 0,65 g/cm3. The resin phenol formaldehyde and the wax sizing were applied in the amount of 6[%] and 1[%], respectively. The pressing cycle was 8 minutes, temperature of 180°C and specific pressure of 40 kgf/cm2. The assays were performed according to standard ASTM D1037 (1993) and DIN 52362 (1982) and the results were evaluated by Analysis of Variance and Scott-Knott Test. As result, it was observed that the best compositions are obtained in the treatment composed exclusively of Pinus spp particles and in the treatment with particles of Pinus spp in the core layer and the E. benthamii in the outer layers. It was verified potential of Eucalyptus benthamii for the production of OSB when mixed with particles of P. taeda and P. eliiottii, considering that in pure panels it showed unsatisfactory results.